2014
DOI: 10.1155/2014/102160
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase-Dependent Recruitment of Neutrophils and Macrophages by Eotaxin-Stimulated Murine Eosinophils

Abstract: The roles of eosinophils in antimicrobial defense remain incompletely understood. In ovalbumin-sensitized mice, eosinophils are selectively recruited to the peritoneal cavity by antigen, eotaxin, or leukotriene(LT)B4, a 5-lipoxygenase (5-LO) metabolite. 5-LO blockade prevents responses to both antigen and eotaxin. We examined responses to eotaxin in the absence of sensitization and their dependence on 5-LO. BALB/c or PAS mice and their mutants (5-LO-deficient ALOX; eosinophil-deficient GATA-1) were injected i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Supporting our hypothesis, the study published by Li et al (2014) showed that 5-LO inhibition improved acute liver failure, and that was associated with reduced macrophage number. Another study by Luz et al (2014) supports our findings of reduced macrophage infiltration in the intestine and liver of both 5-LO–deficient, leukocyte-transplanted mice and zileuton-treated mice. These authors showed that 5-LO inhibition by MK886 reduced recruitment of neutrophils and macrophages into the peritoneal cavity of mice stimulated with eotaxin, demonstrating the importance of the 5-LO pathway for the recruitment of those cells.…”
Section: Discussionsupporting
confidence: 85%
“…Supporting our hypothesis, the study published by Li et al (2014) showed that 5-LO inhibition improved acute liver failure, and that was associated with reduced macrophage number. Another study by Luz et al (2014) supports our findings of reduced macrophage infiltration in the intestine and liver of both 5-LO–deficient, leukocyte-transplanted mice and zileuton-treated mice. These authors showed that 5-LO inhibition by MK886 reduced recruitment of neutrophils and macrophages into the peritoneal cavity of mice stimulated with eotaxin, demonstrating the importance of the 5-LO pathway for the recruitment of those cells.…”
Section: Discussionsupporting
confidence: 85%
“…Eosinophils are the first immune cells to be recruited to the site of injury in response to locally produced eotaxin, and are followed by more numerous neutrophils and macrophages [ 73 ]. As shown in Figure 8 , eotaxin increased 5.4-fold for LPS alone ( p < 0.001, PC) and it was attenuated with FA, which only showed a 4.1-fold increase ( p < 0.01), but not with SF (5.0-fold, p < 0.001) demonstrating that FA was able to show some protective effects in the initial phases of the LPS response.…”
Section: Resultsmentioning
confidence: 99%
“…Male and female BALB/c mice, wild-type ones, and mutants lacking either IL-4 (IL-4 KO; Jackson Laboratory online reference http://jaxmice.jax.org/strain/002496.html ) functional genes or an enhancer element in the promoter region of gene coding for the GATA-1 transcription factor [ 26 ], required for eosinophil-lineage determination (GATA-1 dbl KO or GATA-1 for short; Jackson Laboratory online reference http://jaxmice.jax.org/strain/005653.html ), and C57BL/6 mice, wild-type ones, and mutants lacking iNOS [ 33 , Jackson reference #002596] functional genes were bred at CECAL-FIOCRUZ (Rio de Janeiro, Brazil) and used at 6–8 weeks of age. Animal housing and handling followed procedures approved by the Institutional Committee on Ethical Handling of Laboratory Animals (Licenses CEUA #L002-09; CEUA-CCS-UFRJ #181-13).…”
Section: Methodsmentioning
confidence: 99%
“…IL-17A regulates granulocyte populations by coupling granulocyte clearance from tissues to neutropoiesis in bone-marrow through induction of the granulocyte colony-stimulating factor (G-CSF) [ 24 ]. By contrast, less is known about IL-17A effects on eosinophils, which are closely related to neutrophils [ 25 ] but remain better known for their pathogenetic roles in allergy than for their contributions to antimicrobial defences [ 26 ].…”
Section: Introductionmentioning
confidence: 99%